ANALISIS KADAR TIMBAL (Pb) PADA BERBAGAI TUMBUHAN DI KAWASAN STASIUN PENGISIAN BAHAN BAKAR UMUM (SPBU) KOTA PALU - Muhammad Fajri Ramadhan Muslim Saleh; Miswan Miswan; Riska Septiana (Biology Department, Mathematics and natural science, Tadulako University, 2022)
Exhaust gas produced by motorized vehicles releases lead (Pb) into the environment and can be absorbed into plant tissues. This study aimed to examine the content of lead (Pb) accumulated in leaves. Sampling used purposive sampling as a sampling method at four gas stations in Palu City. Pb levels were determined by atomic absorption spectrophotometry (AAS) at the Laboratory of Analytical and Environmental Chemistry, Department of Chemistry, Faculty of Mathematics and Natural Sciences, Tadulako University. The results showed that the highest to lowest lead absorption in the leaves was Syzygium myrtifolium Walp; 0.75 mg/l from Tawaeli gas station, Bouganvillea spectabilis Willd; 0.67 mg/l from Maluku gas station, Polyalthia longifolia var. pendula; 0.67 mg/l at Yos Sudarso gas stations, and Dracaena reflexa Lam; 0.58 mg/l from Diponegoro gas station. The concentration of lead (Pb) found in each plant from gas stations is still below the maximum threshold set by SNI 01-7387:2009, which is 0.5-3 ppm. The ambient air content around the gas station is still below the air quality standard for measuring the lead (Pb) 2 g/m3 parameter.